KOMPOSISI, FUNGSI DAN NILAI DAMPIANG SURANTIAH - Firda Riki Arta; Awerman Awerman; Zainal Warhat (Institut Seni Indonesia Padang Panjang, 2017)
ABSTRACT This study aims at seeing the composition, function, and value of dampiang that exists in Surantiah people, Pesisir Selatan. Surantiah people use dampiang as the accompaniment in the event of maanta marapulai (= escorting bridegroom). The tradition that performs dampang is known as the name ‘badampiang,’ and it has been practiced hereditarily by people. Dampiang composition will be analyzed by using Kusumawati’s view, that the elements of music composition involve rhythm, melody, harmony, form, and color. Dampiang function will be analyzed by using Alan P. Merriam’s view. The analysis of dampiang value will be conducted by using value proposed by Max Scheler. This study concludes that dampiang is the lyric in the form of pantun that contains messages for the bridegroom. Dampiang composition is formed by flat rhythm and melody built by dampiang harmony. Dampiang has the function as emotional expression, cultural preservation, and societal integration. Dampiang in Surantiah people does not have the function of enjoyment. Dampiang has a value that reflects something believed and considered of by Surantiah people. Value contained in dampiang involves This study is expected to be able to widen the studies about dampiang and other traditional arts. It is also expected to become the part of preservation and development forms of traditional art-culture.